Dinamika Pengaruh Perkembangan E-Commerce terhadap Transformasi Pola Konsumsi Mahasiswa Universitas Katolik Widya Mandira Kupang - Aquilina Deverceli Oki; Cassandra Rosalia Ballo; Elisabeth Theresa YNA; Yohanesa Pemandi Lian (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
The rapid expansion of digital technology has reshaped consumer behavior, especially among students who are highly familiar with online platforms. This study examines how the development of e-commerce influences the transformation of consumption patterns among students at Widya Mandira Catholic University, Kupang. Using a descriptiveexploratory approach supported by survey data, the research explores the level of adoption, purchasing preferences, and behavioral changes that emerge as students increasingly rely on digital shopping platforms. The findings show that e-commerce has become deeply embedded in students’ daily activities, with most respondents indicating a strong preference for online shopping due to accessibility, flexible payment options, and the appeal of promotions and discounts. Reviews and product ratings also play a decisive role in shaping purchasing decisions, reflecting the growing importance of social validation in digital consumption. Alongside these benefits, the study identifies several behavioral shifts, including more frequent purchases, a tendency toward impulsive buying, and challenges in controlling expenses. Despite this, many students report maintaining awareness of these tendencies and attempting to manage their online shopping more responsibly. Overall, the study highlights that e-commerce is not only a practical tool for fulfilling daily needs but also a significant force driving changes in consumption habits among university students in the digital era.